2022
DOI: 10.2147/ijn.s389471
|View full text |Cite
|
Sign up to set email alerts
|

Small Extracellular Vesicles Released from Bioglass/Hydrogel Scaffold Promote Vascularized Bone Regeneration by Transferring miR-23a-3p

Abstract: Background The treatment of critical-size bone defect is a great difficulty in orthopedics. Osteogenesis and angiogenesis are critical issue during the process of bone repair and remodeling. Mesenchymal stem cells (MSCs)-derived exosomes have the same therapeutic effect to MSCs-based therapies. The effect of human umbilical cord MSCs-derived sEVs (hUC-MSCs-sEVs) on vascularized bone regeneration and the potential mechanism remains to be investigated. Herein, we aimed to explore the therapeutic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…MicroRNA(miRNA) is instrumental in regulating gene expression by binding the 3′‐UTR or amino acid coding sequences of the target gene. [ 30 ] To further verify the underlying mechanism of anti‐inflammatory, proteoglycans synthesis and collagen formation mediated by HP‐sEVs, miRNA expression profiles of sEVs and HP‐sEVs were measured by high‐throughput small RNA sequencing. The count number distribution of the total small RNA of sEVs and HP‐sEVs was different ( Figure 5 a ).…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNA(miRNA) is instrumental in regulating gene expression by binding the 3′‐UTR or amino acid coding sequences of the target gene. [ 30 ] To further verify the underlying mechanism of anti‐inflammatory, proteoglycans synthesis and collagen formation mediated by HP‐sEVs, miRNA expression profiles of sEVs and HP‐sEVs were measured by high‐throughput small RNA sequencing. The count number distribution of the total small RNA of sEVs and HP‐sEVs was different ( Figure 5 a ).…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al used GelMA/nanoclay HG with a bioglass scaffold to transfer exosomal miR-23a-3p from UC MSCs for vascularized bone regeneration through the PTEN/Akt pathway. [38] Similarly, Zhang et al revealed that bone repair could be accelerated by enhancing angiogenesis mediated by exosomal miR-21 delivered locally by a HA HG with nanoHAp/poly-𝜖-caprolactone (PCL) scaffold. [39]…”
Section: Large Bone Defects and Fracturementioning
confidence: 99%
“…The commonly used microspheres include liposome vectors, 92 organic carriers (such as polyethyleneimine (PEI), 93 chitosan (CS), 94 gelatin 95 ), inorganic material carriers (such as mesoporous silica nanoparticles (MSNs) 96,97 ), and exosomes. 98,99 Table 2 summarized the preparation of microspheres loaded with bioactive substances and their effect on vascular osteogenesis. The binding of microspheres loaded with bioactive substances on the scaffold surface mainly includes electrostatic adsorption and chemical binding.…”
Section: Binding Of Microspheres Loaded With Bioactive Substances On ...mentioning
confidence: 99%